Transfer of Additive Chemicals From Marine Plastic Debris to the Stomach Oil of Northern Fulmars - Kühn, Susanne; Booth, Andy M.; Sørensen, Lisbet; van Oyen, Albert; van Franeker, Jan A. (Frontiers in Environmental Science, 2020)
For this study, the transfer of plastic additives to stomach oil of northern fulmars (Fulmarus glacialis) has been investigated. Procellariiform seabirds retain oily components of their prey in theirs stomach as a means to store energy. A marine litter-derived microplastic reference mixture and separately a marine litter-derived polystyrene sample were added to stomach oils in an experiment. A total of 15 additives, including plasticizers, antioxidants, UV stabilizers, flame retardants, and preservatives were identified in the original plastic mixtures, and monitored in the leachates. These substances include those known for endocrine disruptive, carcinogenic and/or other negative effects on organisms. Stomach oil was exposed to these plastic materials and was sampled during a long-term experiment (0, 14 and 90 days exposure of plastic particles in stomach oil) and a subsequent short-term detailed study (8 hours, 1, 2, 4, 8 and 21 days). Five of the monitored substances were shown to strongly leach from the microplastic reference mixture into the stomach oil during the experiment. Four substances were identified in a marine litter-derived polystyrene foam, of which two leached into stomach oil. Leaching of harmful plastic additives to the stomach oil of fulmars may be of concern, as fulmars regularly ingest plastics which are retained and gradually ground in the gizzard before passage to the intestines and excretion.